Omissão de macronutrientes no crescimento e no estado nutricional de plantas de repolho cultivado em solução nutritiva - Avalhaes, Cintia Carla [UNESP]; Prado, Renato de Mello [UNESP]; Romualdo, Liliane Maria [UNESP]; Rozane, Danilo Eduardo; Ribeiro Correia, Marcus Andre (Universidade Federal de Uberlândia (UFU), 2009)
Given the importance of heart, especially among the high brassica consumption, coupled with the scarcity of studies that report symptoms of nutritional disorders in the culture, the work was carried out to evaluate the effect of the omission of macronutrients in the development and nutritional status of cabbage, and describe visual symptoms of nutritional deficiency. The experiment was conducted under greenhouse conditions in the UNESP, Jaboticabal, SP. The experiment was arranged in completely randomized design with three replications and seven treatments, corresponding to complete nutritive solution (macro and micronutrients) and individual N, P, K, Ca, Mg and S omission. Plant height, number of leaves, leaf area, shoot, root and whole plant dry mass and macronutrient levels were determined and nutritional deficiency symptoms were described. Individual omissions of N, P, K or Ca were limiting for cabbage growth, considerably reducing plant height, number of leaves, and shoot, root and whole plant dry mass. Nutritional deficiency symptoms were observed for each element. Shoot macronutrient levels in control and nutrient omission treatments were, respectively: N = 31.0-11.9; P = 5.3-0.60; K = 63.5-4.8; Ca = 25.9-4.8; Mg = 5.2-0.5; S = 10.3-1.4 g kg(-1).

Dada a importância do repolho, destacando-se dentre as brássicas pelo alto consumo, aliada à escassez de pesquisas que relatem sintomatologia de desordens nutricionais na cultura, realizou-se o trabalho com o objetivo de avaliar o efeito da omissão de macronutrientes no desenvolvimento e no estado nutricional do repolho, assim como descrever sintomas visuais de deficiência nutricional. O experimento foi conduzido em casa de vegetação da UNESP, Campus de Jaboticabal, SP. O delineamento experimental foi inteiramente casualizado, com sete tratamentos, que corresponderam à solução completa (macro e micronutrientes) e à omissão individual de N, P, K, Ca, Mg e S, com três repetições, sendo uma planta por parcela. Avaliou-se a altura das plantas, número de folhas, área foliar, matéria seca da parte aérea, das raízes e planta inteira, teores dos macronutrientes da parte aérea e raízes, e descrição das desordens nutricionais. As omissões individuais de N, P, K, Ca e Mg foram limitantes para o crescimento vegetativo do repolho, reduzindo consideravelmente a altura das plantas, o número de folhas, área foliar e matéria seca da parte aérea, raízes e planta inteira. Foram observados sintomas de deficiência nutricional de cada elemento. Os teores dos macronutrientes na parte aérea do tratamento completo e com omissão dos nutrientes foram, respectivamente, N = 31,0 – 11,9; P = 5,3 – 0,60; K = 63,5 – 4,8; Ca = 25,9 – 4,8; Mg = 5,2 – 0,5; S = 10,3 – 1,4 g kg-1.
Omission of macronutrients of the growth and nutritional status of plants of cabbage grown in nutrient solution
Keywords: Brassica oleraceae; Nutritional deficiency; Mineral nutrition; Development